Superconducting binary hydrides: Theoretical predictions and experimental progresses. (November 2021) - Gao, Guoying; Wang, Linyan; Li, Mingtao; Zhang, Jinbo; Howie, Ross T.; Gregoryanz, Eugene; Struzhkin, Viktor V.; Wang, Lin; Tse, John S.
Abstract: Hydrogen, the lightest element in the periodic table, has been predicted to metalize under extreme compression. Metallic hydrogen is believed to be a room-temperature superconductor. Due to the considerable experimental challenges of reaching such a state, the metallic hydrogen has often been deemed the holy grail of condensed matter physics. It was then predicted that hydrogen-rich hydrides could also become superconductors with high critical temperatures ( T c ) at substantially lower pressures than that of pure hydrogen. In the past decade, there has been significant progress in this field of research from both theoretical and experimental viewpoints. An exemplary of these research efforts is the recent superconducting binary hydride with a record T c of ∼260 K, a promising result for the eventual discovery of a room-temperature superconductor. This review summarizes significant developments in the studies of binary hydrides at high pressure that were predicted to exhibit superconductivity. In particular, those that have been experimentally verified or have calculated T c > 100 K. Such hydrides are often characterized by unique, hydrogen-rich stoichiometry and interesting structural arrangements. This recent progress in the field allows a modern perspective on the potential of reaching a room temperature superconducting state. Graphical abstract: Image 1 Highlights: This review summarizes the most recent experimental progresses of superconducting binary hydrides. This review summarizes the major developments in binary hydrides who have T c > 100 K. The relationship among superconductivity and stoichiometry and structures. A perspective on the potential of reaching a room temperature superconducting state. The authors are leading scientists in the field and have made fundamental contributions.